2019
DOI: 10.29244/jpsl.9.2.304-313
|View full text |Cite
|
Sign up to set email alerts
|

KEANEKARAGAMAN SPESIES HERPETOFAUNA PADA BERBAGAI TIPE TUTUPAN LAHAN DI LANSEKAP PERKEBUNAN SAWIT: Studi Kasus di PT. BLP Central Borneo

Abstract: The expansion of oil palm plantations in Indonesia is often blamed as the drivers of natural resource destruction and decrease the tropical biodiversity. Herpetofauna is one of biodiversity on oil palm plantation, but information about its species diversity is still limited. This research was aims to reveal the variation of diversity of Herpetofauna on oil palm landscape in central Borneo. Field inventory was conducted on seven types of land cover i.e. young oil palm, mature oil palm, old oil palm, High Conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 9 publications
1
8
3
5
Order By: Relevance
“…This finding is not surprising because this species likes areas that have sufficiently thick bushes and grasses (Kamsi et al 2017). The number of T. sexlineatus individuals found in this study was higher than that reported by Kwatrina et al (2019) in the Landscape of oil palm plantation, i.e., 1 individual, presumably because the rubber plantation in Lubuklinggau had grasses, making it an ideal habitat for T. sexlineatus.…”
Section: Species Compositioncontrasting
confidence: 82%
See 2 more Smart Citations
“…This finding is not surprising because this species likes areas that have sufficiently thick bushes and grasses (Kamsi et al 2017). The number of T. sexlineatus individuals found in this study was higher than that reported by Kwatrina et al (2019) in the Landscape of oil palm plantation, i.e., 1 individual, presumably because the rubber plantation in Lubuklinggau had grasses, making it an ideal habitat for T. sexlineatus.…”
Section: Species Compositioncontrasting
confidence: 82%
“…The presence of water, bushes, litter, and lush trees around the settlements make an ideal place for herpetofauna to live. The moist microhabitat, due to the tight canopy cover and lots of litter, becomes an influential factor on herpetofauna especially for amphibians (Wanger et al 2011;Qurniawan 2015;Kwatrina et al 2019).…”
Section: Ecological Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Herpetofauna memiliki peran terhadap fungsi kesuburan tanah, siklus nutrisi, pengurai biji, penyerbukan tumbuhan, dan sebagai predator dalam jaring-jaring makanan (Hocking & Babbit, 2014;Cortés-Gomez, Ruiz-Agudelo, Valencia-Aguilar, & Ladle, 2015). Menurut Kwatrina, Santosa, & Maulana (2019), keanekaragaman herpetofauna di perkebunan sawit dipengaruhi oleh ragam habitat. Selain itu, pertumbuhan, daya tahan, dan reproduksi herpetofauna juga dapat dipengaruhi oleh faktor lingkungan yang berdampak pada perubahan populasinya (Alford & Richards, 1999).…”
Section: Pendahuluanunclassified
“…Setiap tipe tutupan lahan dibuat satu transect jalur dengan panjang 1 km dan lebar area pengamatan selebar 75 m ke arah kanan dan kiri jalur. Data yang diambil meliputi jenis yang ditemukan, jumlah herpetofauna, waktu perjumpaan, tumbuhan bawah, sumber air, suhu, dan kelembapan (Kwatrina et al, 2019).…”
Section: Metode Penelitianunclassified